2020
DOI: 10.1111/lam.13407
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contaminants and their antibiotic susceptibility patterns in ready‐to‐eat foods vended in Ogun state, Nigeria

Abstract: Contamination of ready‐to‐eat (RTE) foods by pathogenic bacteria may predispose consumers to foodborne diseases. This study investigated the presence of bacterial contaminants and their antibiotic susceptibility patterns in three locally processed RTE foods (eko, fufu and zobo) vended in urban markets in Ogun state, Nigeria. Bacteria isolated from a total of 120 RTE food samples were identified by 16S rRNA gene phylogeny while susceptibility patterns to eight classes of antibiotics were determined by the disc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
(55 reference statements)
2
8
0
Order By: Relevance
“…The results obtained correlate with the previous work of Cardonha et al 41 who reported the isolation of resistant E. coli strains to more than one antibiotic from water samples. Also, the test bacterium, K. pneumoniae in this study was slightly sensitive to gentamicin which correlates with the previous work of Makinde et al 42 .…”
Section: Discussionsupporting
confidence: 92%
“…The results obtained correlate with the previous work of Cardonha et al 41 who reported the isolation of resistant E. coli strains to more than one antibiotic from water samples. Also, the test bacterium, K. pneumoniae in this study was slightly sensitive to gentamicin which correlates with the previous work of Makinde et al 42 .…”
Section: Discussionsupporting
confidence: 92%
“…In developing countries such as Burkina Faso, numerous studies have previously reported the presence of Salmonella spp. in RTE foods [30][31][32]. Te potential hygiene breakdowns at various stages of the food processing and distribution chain due to the lack of food safety regulations and food handler educations are responsible for food contamination in developing countries [33].…”
Section: Presumptive Salmonella Isolates and Molecularmentioning
confidence: 99%
“…Bacteria are primary contaminants of ready-to-eat (RTE) foods ( 1 ), and strains resistant to antibiotics constitute a major public health concern. Here, we report the draft genomes of Shiga toxin-producing Escherichia coli (STEC) strains IPK9(1) and IKS1(2), which were isolated from kokoro and shawarma, respectively, sold in Lagos, Nigeria, and were screened phenotypically against eight antibiotics.…”
Section: Announcementmentioning
confidence: 99%
“…One milliliter of the homogenate was spread plated on nutrient agar (NA) (Sigma-Aldrich, Germany) and incubated at 37°C for 18 to 24 h. Pure colonies were subcultured on NA and subsequently on Mueller-Hinton agar for phenotypic antibiotic susceptibility testing using a set of eight antibiotics. The two strains recorded multiple antibiotic resistance index values ( 1 ) of 0.8 and 0.5, as described by CLSI guidelines ( 1 ), were subcultured in nutrient broth, and were grown overnight at 37°C in a shaking incubator at 220 rpm. The broth culture was centrifuged and washed in phosphate-buffered saline at 10,000 × g .…”
Section: Announcementmentioning
confidence: 99%